Enhancing library services with artificial intelligence: innovations, challenges, and impacts - Hamam, Kamiliya Iksana; Fahmi, Faisal; Abd Aziz, Nor Erlissa; Mokhtar, Siti Aishah; Mohd Affandi, Najatul Afiqah (Faculty of Information Management, 2025)
The challenges faced in implementing artificial intelligence (AI) in both significant potentials to improve library operations, barriers such as financial constraints, lack of technical expertise, and concerns over data privacy and security hinder its full adoption. To address these issues, this study examines the innovations, challenges, and impacts of AI implementation in library services. A systematic literature review was conducted following PRISMA 2020 guidelines, with data collected from Scopus, ProQuest, and Web of Science databases. Five key studies were published between 2019 and 2024 were analyzed. The findings reveal that AI has greatly enhanced library operations through applications such as automated cataloging, virtual assistants for real-time user support, and IoT-based resources management systems. However, financial and technical challenges, as well as privacy concerns, continue to limit broader implementation. Despite these obstacles, AI adoption has improved operational efficiency and user satisfaction. To maximize AI's benefits, libraries require targeted strategies, including increased funding, staff training, and infrastructure development. Future research should focus on the ethical and sustainable use of AI to ensure widespread accessibility and responsible implementation.